2000
DOI: 10.1034/j.1600-0706.2000.900201.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation variation in reproductive traits of female masu salmon, Oncorhynchus masou

Abstract: Tamate, T. and Maekawa, K. 2000. Interpopulation variation in reproductive traits of female masu salmon, Oncorhynchus masou. -Oikos 90: 209 -218.Several life history models predict that larger eggs and lower fecundity should be favored in a low-growth environment. We applied the model of Sibly et al. to seven Japanese populations of masu salmon (Oncorhynchus masou) in order to test the predictions that populations in which individual growth rate is low are characterized by larger eggs and lower fecundity. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 39 publications
6
65
2
Order By: Relevance
“…Because fecundity (n) is assumed to be equivalent to R/z, the optimal strategy changes z to maximize R/z and therefore, a reduction in growth will lead to an increase in optimal propagule size. Tamate and Maekawa (2000) showed that adverse conditions (e.g. low resource availability) may also directly influence R, assuming that the effect of lower reproductive investment is analogous to that of low growth conditions in the model of Sibly et al (1988), and will therefore result in an identical change in optimal propagule size as for low growth conditions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because fecundity (n) is assumed to be equivalent to R/z, the optimal strategy changes z to maximize R/z and therefore, a reduction in growth will lead to an increase in optimal propagule size. Tamate and Maekawa (2000) showed that adverse conditions (e.g. low resource availability) may also directly influence R, assuming that the effect of lower reproductive investment is analogous to that of low growth conditions in the model of Sibly et al (1988), and will therefore result in an identical change in optimal propagule size as for low growth conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Models of life history theory predict that in low-growth and/or low-reproduction environments, the release of larger but fewer offspring will be favoured (Sibly and Calow 1986;Lloyd 1987;McGingley et al 1987;Stearns 1992;Tamate and Maekawa 2000). The optimal egg size and number of offspring that individuals of a population will produce, depend on the balance between the production of larger eggs, which in general survive better, mature earlier and develop faster (review in Fox and Czesak 2000) and the production of smaller eggs, which results in a higher fecundity (Bernardo 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1). The first strategy appears to be common among ectotherms because females in colder environments tend to produce larger eggs (Perrin 1988;Iguchi and Yamaguchi 1994;Glazier 1999;Ernsting and Isaaka 2000;Tamate and Maekawa 2000;Kim and Thorpe 2001; reviewed by Atkinson et al 2001). Moreover, selection experiments involving Drosophila melanogaster have been used to link the evolution of large eggs directly to low environmental temperature (Azevedo et al 1996).…”
mentioning
confidence: 99%
“…Crossin et al (2004) reported that egg size was reduced in sockeye populations performing particularly energydemanding migrations, and Braun et al (2013) reported that in years of energetically demanding migration conditions, female sockeye salmon produced smaller eggs for their size than in years when conditions were more benign. Jonsson et al (1996) reported that Atlantic salmon egg size changes with juvenile growth rate, and similar relationships have been reported for some other salmonids (Morita et al 1999, Tamate & Maekawa 2000, but not for brown trout Salmo trutta (Jonsson & Jonsson 1999) or some Pacific salmonids Oncorhynchus spp. (Quinn et al 2004(Quinn et al , 2011.…”
Section: Discussionmentioning
confidence: 56%